Pengaruh Kualitas Pelayanan terhadap Kepuasan Wisatawan pada Swiss-Belhotel Ambon - Rehatta, Geradin (Jurnal Ilmiah Aset, 2018)
This study aims to determine the effect of tangible, reliability, responsiveness, assurance, and emphaty to tourist satisfaction. The research method used in this research is explanatory research. Analysis of the data used is multiple regression. The population of this study were all visitors who stayed at the Swiss-belhotel Ambon in July 2017. The sample of this study was taken using purposive sampling method to obtain a sample of 50 tourists. The results showed that in the partial test of tangible, reliability, responsiveness, assurance, and emphaty had a positive effect on tourist satisfaction.